ANALISIS KONSENTRASI LOGAM BERAT PADA KERANG SIMPING (PLACUNA PLACENTA) DAN AIR SEBAGAI INDIKATOR KUALITAS PERAIRAN MUARA SUNGAI INDRAGIRI - Itje Lestari; Bintal Amin Amin; Marnis Marnis (Program Pascasarjana Universitas Riau, 2019)
This research was conducted in March – April 2018 in the waters of Indragiri River estuary. This study aims to analyze the concentration of Pb, Cd, Cu and Zn in water and scallop (Placuna placenta) and to calculate the safety limit in consuming the scallop from the estuary. Sampling was done at 6 stations and analysis of heavy metals concentration was performed by AAS Shimadzu AA-7000. The results of the study showed that the concentration of heavy metals between stations varied but the concentrations between stations in outer part and inner part of the estuary was not significantly different (p>0.05). The average concentration of Pb, Cd, Cu and Zn in surface water were 0,0744; 0,0038; 0,0302; 0,1761 mg/L, and in scallop were 0,3100; 0,5300; 7,8669; 43,1069 µg/g, respectively. Heavy metals concentration in water and scallops shows positive correlations, except Pb. Based on the calculation of PTWI, it is recommended to consume the scallop from Indragiri river estuary of not more than 22,58 kg/week (Pb); 3,69 kg/week (Cd); 124,57 kg/week (Cu) and 45,46 kg/week (Zn).